The Debate on the Constitution : Federalist and Antifederalist speeches, articles, and letters during the struggle over ratification. Part Two. Debates in the press and in private correspondence ; Debates in the State ratifying conventions - Bailyn, Bernard (Library of America ; 62)
"Bernard Bailyn selected the contents and wrote the headings and notes...." (p. v)